PENGARUH GAYA BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS XI IPS SMA NEGERI 5 PADANGSIDIMPUAN - Erlina Sari (Institut Pendidikan Tapanuli Selatan, 2019)
This study aims to look at the effect of learning styles together on student achievement on economic subjects in class XI IPS Padangsidimpuan 5 High School. The research method used is descriptive method. Population Class XI Department of Social Sciences 2017/2018 Academic Year in 2 Padangsidimpuan Public High Schools in 2 classes consisting of 62 people. The sampling technique taken is the total sampling technique. Data collection techniques used were questionnaires and tests. Data analysis techniques used are simple regression formulas and multiple regression. The research conducted in XI IPS class at Padangsidimpuan 5 High School found that F count was 3.683 with a significance level of 0.017. While the F table at the confidence level of 95% (α = 0.05) is 2.626. Therefore in both calculations, F count> F table and the level of significance (0.017 <0.05) shows that the influence of independent variables (visual, auditory and kinesthetic learning styles) is jointly significant towards the students' achievement in economic subjects in the class XI IPS SMA N 5 Padangsidimpuan. This means that the variables of visual, auditory and kinesthetic learning styles become one of the driving variables so that student learning achievement increases especially towards student learning achievement on economic subjects. So students who are able to utilize their learning styles to the maximum both visual, auditory, and kinesthetic learning styles will be able to improve their learning achievement, especially on economic subjects.